Pengaruh Penambahan Bubuk Cengkeh (Syzygium aromaticum) Sebagai Pengawet Alami Terhadap Daya Simpan Selai Cempedak (Artocarpus campeden) - Norsela, Riska; Hafizah, Ellyna; Irhasyuarna, Yudha (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of clove powder on the shelf life of day 1 and day 5, pH levels, water content, and sensory testing of cempedak jam. This study used (CRD) with 4 formulations with different concentrations of clove powder. The formulations were P0 (0% clove powder), P1 (0.2% clove powder), P2 (0.4% clove powder), and P3 (0.6% clove powder). This study used four kinds of analysis consisting of a five-day shelf-life physical observation test, pH, moisture content, and sensory test. Sensory test analysis was carried out on samples of cempedak jam on day 0, but for physical observation analysis, pH, and water content were carried out on cempedak jam with storage on day 1 and day 5. Data analysis on pH and moisture content using One-Way ANOVA statistics was followed by the Tukey test and the sensory test using the Kruskal-Wallis statistic followed by a hypothesis test with a summary test. The use of clove powder can affect the shelf life, more the concentration of clove powder in cempedak jam, the longer shelf life of the jam. The more concentration of clove powder, the acidity (pH) and water content will increase. The sensory test results showed that the concentration of clove powder affected the parameters of color, taste and aroma of cempedak jam.